Factors Affecting the Taqdir of Ellipsis/Hadhf in the Tafsir Tradition - Kaya, Aykut (Cumhuriyet Univ, Fac Theology, 2025)
This study examines the factors that influence the interpretion (taqdir) of elliptical (hadhf) expressions in the Qur'an within the tafsir tradition. The central problem of this study revolves around the question of what underlying reasons account for the different forms of taqdir of hadhf expressions in the Qur'an within the tafsir literature, which factors guide exegetes (mufassirs) toward these interpretations. The study aims to examine the underlying motives that guide the taqdir of hadhf expressions and to analyze these factors systematically illustrative examples. At the same time, the study seeks to determine whether the exegetes act in accordance with methodological principles and scholarly traditions when engaging in the taqdir of Qur'anic verses, rather than making arbitrary judgments based on personal subjectivity. In the existing literature, there are various studies addressing the reasons behind interpretive differences in tafsir and the concept of hadhf and its taqdir. However, there appears to be a notable lack of dedicated research that systematically investigates the factors giving rise to these interpretations. In this respect, the present study aims to make an original contribution to the field by identifying, in a comprehensive and systematic manner, the underlying dynamics that guide the method of taqdir, an approach that contributes to the richness of interpretation within the tafsir tradition. The study also aims to shed light on the underlying dynamics that give rise to the richness and diversity of meanings found in the interpretation of Qur'anic verses within the tafsir tradition. In line with the subject and objectives of the study, hadhf expressions were examined in detail, the factors guiding their taqdir were identified, and a principled framework was established through well-grounded examples with high representational value. According to the findings, two primary factors underlie the varying taqdir choices of exegetes regarding elliptical expressions: influences stemming from the structural features of the Qur'anic text and influences arising from the exegetes' own subjectivities. First and foremost, it should be noted that the structural characteristic of the Qur'anic text allows for such diversity in interpretive approaches. Firstly, it should be noted that methodological assumptions such as the manner of the Qur'an's revelation open the door to different interpretations. Furthermore, the lack of clear contextual indicators (qarinah) for the presence of hadhf in many verses has enabled exegetes to identify different clues based on their own ijtihad, thereby leading them to adopt various forms of taqdir. Similarly, the ambiguity regarding the addressees in many elliptical verses has led exegetes to adopt varying interpretations depending on their understanding of the intended audience. Additionally, reports concerning the occasions of revelation (asbab al-nuzul) and the Prophet's practices-both of which relate to the external context of the verses-also function as key factors guiding the taqdir process. Exegetes have tended to prefer interpretations that align with these reports and prophetic practices. The second main factor contributing to the variation in taqdir within the tafsir tradition can be attributed to the juristic (fiqhi), theological (kalami), political, and sectarian (madhhabi) convictions held by the exegetes. It has been observed that exegetes interpret hadhf expressions in accordance with the fiqhi school, their political views, and doctrinal stance to which they adhere. Notably, issues on which different opinions exist among the madhhabs such as ru'yatullah (the vision of God) and 'ismah al-anbiya' (the infallibility of the prophets) have led exegetes to divergent interpretations. Consequently, it is understood that while exegetical subjectivity plays a role in the interpretive process of elliptical expressions, this subjectivity is not arbitrary but shaped by specific factors.
Keywords: Tafsir; Ellipsis/Hadhf; Interpretation/Taqdir; Methodology; Interpretive Differences